The influence of incline and speed on work rate, gross efficiency and kinematics of roller ski skating - Sandbakk, O.; Ettema, G.; Holmberg, H. C. (European Journal of Applied Physiology, 2012)
During competitions, elite cross-country skiers produce higher external work rates on uphill than on flat terrain. However, it is not presently known whether this reflects solely higher energy expenditure. Furthermore, the kinematic factors associated with these higher rates of uphill work have not yet been examined. Therefore, in the present investigation the work rate and associated kinematic parameters at similar metabolic rates during roller ski skating on flat and uphill terrains have been compared. Seven elite male skiers performed six 5-min sub-maximal exercise bouts at the same low, moderate and high metabolic rates on 2 and 8% inclines, while roller skiing on a treadmill employing the G3 skating technique. The work rate was calculated as work against gravity and friction, whereas the energetic equivalent of VO2 was taken as the metabolic rate. Gross efficiency was defined as work rate divided by metabolic rate. Kinematic parameters were analyzed in three dimensions. At the same metabolic rate, the work rate, cycle rate, work per cycle and relative duration of propulsive phases during a cycle of movement were all higher on the 8% than on the 2% incline at all speeds (all P < 0.05). At similar work rates, gross efficiency was greater on the 8% incline (P < 0.05). In conclusion, these elite skiers consistently demonstrated higher work rates on the 8% incline. To achieve the higher work rates on the steeper incline, these elite skiers employed higher cycle rates and performed more work per cycle, in association with a longer relative propulsive phase.